Pengobatan Tradisional Untuk Menyembuhkan Demam Pada Anak dalam Naskah Buku Isi Warni Warni - Konia Latifah; Ken Widyatwati (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
The manuscript entitled Buku Isi Warna Warni is a manuscript that contains many traditional medicine ingredients such as medicine for fever in children. The purpose of this study is to present edits and translations of fever treatment texts in children contained in the BIWW manuscript and explain the function of traditional medicine contained in the manuscript. The methods used in this study are data collection, data processing, data analysis and presentation of data analysis results. At the data collection stage, field studies and literature studies are carried out. The data processing stage, philological work steps are carried out from manuscript description, transliteration, editing and translation. In studying the content of the content, a pragmatic approach is used. The source of the data used is the BIWW manuscript which is still written in Javanese script and is stored at the Demak Regency Library and Archives Office. The result of this study is the editing of text that has been cleared of errors and the translation of the text into Indonesian. In addition, there is a function of traditional medicine, especially the treatment of fever in children. This function is the function of education on the types of fever that are often suffered. As for the function of knowledge about herbal medicines derived from plants and other complementary ingredients. In addition, it is also described how to mix herbs and effective methods used to give fever medicine ingredients to children. The functions contained in the BIWW text are still relevant because they can be applied as treatment in today's society. Keywords: BIWW script; traditional medicine: philology; pragmatics; child fever.